Unidade de ensino potencialmente significativa no estudo problematizador dos efeitos fotoelétrico e fotovoltaico - Pereira, Mateus Patrício Barbosa (2019)
In this work, we present a proposal focused on the teaching of Modern and Contemporary Physics, more specifically, for photoelectric and photovoltaic effects. The main objective of the work is the development of a Potentially Significant Teaching Unit (UEPS) that contemplates the teaching of the photoelectric and photovoltaic effect in elementary schools. We develop the activities based on theories of David Ausubel and the studies of Moreira (2011) on the units of education. In the first chapter of the paper, we made an introduction about the main topics to be discussed in the research, as well as presenting the motivation that led to this study. The second chapter is aimed at an approach to the theoretical methodological framework that gave base to this work, that is, the researches and studies of Moreira on the Units of Education. In the third chapter, we briefly present a physics approach involved in the study of semiconductors, exposing the main characteristics and properties of these materials and the applications of this study to the understanding of some phenomena observed in the teaching sequence. In the fourth chapter, we report the experiences of the study and also the results achieved after application of the proposal in the classroom. The research had a qualitative approach and the main audience was students of the final series of High School, 3rd Year of High School. Finally, we present our final considerations on the use of the teaching unit developed, as well as we point out perspectives for future work.